1975
DOI: 10.1111/j.1469-8137.1975.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

CYTOGENETIC STUDIES IN THE GENUS POTENTILLA L.

Abstract: Cytogenetic studies involving eighteen species of Potentilla of the section Gymnocarpae were made to investigate their phylogenetic relationships and to see whether any correlation exists between morphology and crossing relationships.The chromosome numbers of Potentilla ambigens Greene {zn = 82) and P. montenegrina Pant, {zn = 28) were determined for the first time. New intraspecific chromosome races were observed in three species: P. pennsylvanica L. (2« = 42), P. astrisanguinea Lodd. {zn = 84) and P. grandif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 19 publications
0
8
0
2
Order By: Relevance
“…Hybridization has been mainly described in some taxa of subgenus Potentilla (Müntzing and Müntzing, 1941;Guillén et al, 2005). Members of the genus Potentilla represent an extensive polyploidal group with its chromosome number (n) being always a multiple of seven (Ball et al, 1968;Goswami and Matfield, 1975;Eriksson et al, 1998).…”
Section: Laevigatin Bmentioning
confidence: 99%
“…Hybridization has been mainly described in some taxa of subgenus Potentilla (Müntzing and Müntzing, 1941;Guillén et al, 2005). Members of the genus Potentilla represent an extensive polyploidal group with its chromosome number (n) being always a multiple of seven (Ball et al, 1968;Goswami and Matfield, 1975;Eriksson et al, 1998).…”
Section: Laevigatin Bmentioning
confidence: 99%
“…Holm and Ghatnekar (1996) obtained similar results after interspecific crosses between diploid Potentilla argentea and hexaploïd P. argentea and P. collina (4.7% mean germination rate on 10 different interspecific crosses). Acharya Goswami and Matfield (1975) obtained only four hybrids of 628 crosses with three different interspecific crosses between Potentilla species (including P. grandiflora). The high number of pure P. delphinensis plants (36) resulting from crosses in which PD was the mother strongly suggested facultative apomixis in that species, similarly to several Potentilla that are known to be facultative apomictic (Acharya Goswami and Matfield 1975;Holm and Ghatnekar 1996;Nylehn et al 2003;Richards 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Acharya Goswami and Matfield (1975) obtained only four hybrids of 628 crosses with three different interspecific crosses between Potentilla species (including P. grandiflora). The high number of pure P. delphinensis plants (36) resulting from crosses in which PD was the mother strongly suggested facultative apomixis in that species, similarly to several Potentilla that are known to be facultative apomictic (Acharya Goswami and Matfield 1975;Holm and Ghatnekar 1996;Nylehn et al 2003;Richards 2003). Selfing resulting from error of manipulation or unwanted insect pollination could not be totally excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The basic chromosome number for the genus Potentilla is n : 7 (Robertson 1974;Goswami and Matfield 1975 (Mulligan 1959;Darlington and Wylie 1956). An exception is Asker (1970a) (Gray 1889 (Frankton and Mulligan 1970 (Darlington et al 1940 No insects that infest other plants have been reported on P. recta, P. norvegica or P. argentea.…”
Section: Namementioning
confidence: 99%